Alzheimer's disease: The amyloid hypothesis on trial. (January 2016) - Harrison, Judith R.; Owen, Michael J.
Summary: The pathogenesis of Alzheimer's disease is complex. The amyloid hypothesis has directed research efforts for many years, but it has recently been questioned after failed drug trials. Here, we review the evidence for and against and suggest that it might be premature to abandon the amyloid hypothesis.